MicroRNAome: Potential and Veritable Immunomolecular Therapeutic and Diagnostic Baseline for Lingering Bovine Endometritis - Oladejo, Ayodele Olaolu; Li, Yajuan; Wu, Xiaohu; Imam, Bereket Habte; Shen, Wenxiang; Ding, Xue Zhi; Wang, Shengyi; Yan, Zuoting (Frontiers in Veterinary Science, 2020)
Bovine endometrium is a natural pathogen invasion barrier of the uterine tissues’ endometrial epithelial cells that can resist foreign pathogen invasion by controlling the inflammatory immune response. Some pathogens suppressed the innate immune system of the endometrium leading to prolong systemic inflammatory response through the blood circulation or cellular degradation results in bovine endometritis by bacterial endotoxins. microRNA (miRNA) typically involves gene expression in multicellular organisms in post-transcription regulation by affecting both the stability and translation of messenger RNA. Accumulated evidence suggests that miRNAs are important regulators of genes in several cellular processes. They are a class of endogenous non-coding RNAs, which play pivotal roles in the inflammatory response of reproductive diseases. It implicates some miRNAs in the occurrence of bovine endometritis, resorting to regulating the activities of some inflammatory cytokines, chemokine, differentially expressed genes, and protein through modulating of specific cellular signal pathways functions. Studies confirmed that miRNAs play a key regulatory role in various inflammatory diseases by mediating the molecular mechanism of endometrial inflammatory cytokines via signal pathways. This review dwells on improving the knowledge of the role of miRNAs involvement in inflammatory response as to early diagnosis, control, and prevention of bovine endometritis and consequently enlightened on the molecular improvement of the genes coded by various differentially expressed miRNA through the need to adopt recent genetic technologies and development of new pharmaceutical preparations.